Institutional Ownership in Encouraging Carbon Emission Disclosure for Mining Companies, Basic Industries and Chemicals in Indonesia - KISWANTO, Kiswanto; WIDHIASTUTI, Ratieh; SAFITRI, Mila Anggi (Journal of Environmental Management and Tourism; Vol 14 No 3 (2023): JEMT, Volume XIV, Issue 3(67), Summer 2023, 2023)
This research analyses the effect of institutional ownership in strengthening the effect of environmental performance, regulators, and media exposure on carbon emissions disclosure. By using certain criteria in sampling, the unit of analysis was obtained from as many as 57 companies. The research focused on mining, basic industry, and chemical companies listed on the Indonesia Stock Exchange in 2018-2020. Hypothesis testing was carried out using moderated regression analysis which was strengthened by descriptive analysis for each research variable. In general, it is found that the carbon emissions disclosure in the research object is classified as low, with an average disclosure of 7-8 items out of 18 items that must be disclosed in the report. Hypothesis testing shows that environmental performance and media exposure have a positive effect on carbon emissions disclosure, while regulators have no effect on carbon emissions disclosure. The presence of institutional ownership as a moderating variable was found to be able to strengthen the influence of regulators in increasing the carbon emissions disclosure, but not able to strengthen the effect of environmental performance and media exposure on the carbon emissions disclosure. This research contributes to regulators, developing standards for carbon emissions disclosure for companies that go public. Further researchers are expected to add other variables that can affect the carbon emissions disclosure and increase the research period to get more accurate results.